TPACK-Enhanced Geometry and Algebra for Primary School Teacher of KKG Cluster IV in X Koto Singkarak District, Solok Regency - Rara Sandhy Winanda (Fakultas MIPA Universitas Negeri Padang, 2023)
In elementary school, a mastery of geometric and algebraic mathematical methods is necessary. Students in the discipline of algebra struggle with fraction addition and multiplication. Similarly, students struggle in geometry to compute the area of a flat plane. Group IV Koto Sani teachers in the Koto Singkarak District of the Solok Regency received this assistance in the form of workshops. From August to October 2022, there will be three meetings both in-person and online. The offered material is comprised of TPACK-based learning resources, such as Cuisenaire rods, flat media, and music boards. Based on the results of the initial and final surveys, it was determined that there was a 7% improvement in material comprehension, a 7% improvement in the ability to create media, and a 5% improvement in the ability to use media